LOGICALLY, RATIONALITY AND TRUTH IN THE MYTH - Топалова, С.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
This article explores the major approaches to understanding the nature and role of myth in connection with the chronological sequence of types and a desire to see some experience in the myth and the way of display reality. Showed the specifics of the transformation of the myth and its interpretations. Isolated rational, logical, political components of the myth and features of their vision in various interpretations. Using concrete examples illustrate the similarities between archaic mythological subjects and characteristics of the political consciousness of modern man.